Ionic dynamics of the cation in organic–inorganic hybrid compound (CH3NH3)2MCl4 (M = Cu and Zn) by 1H MAS NMR, 13C CP MAS NMR, and 14N NMR. Issue 33 (22nd May 2018) - Lim, Ae Ran
Abstract : The ionic dynamics of (CH3 NH3 )2 MCl4 (M = Cu, Zn) by 1 H MAS NMR, 13 C CP MAS NMR, and 14 N NMR are investigated as a function of temperature with a focus on the role of the CH3 NH3 + cation. Abstract : The ionic dynamics of (CH3 NH3 )2 MCl4 (M = Cu, Zn) by 1 H magic-angle spinning (MAS) nuclear magnetic resonance (NMR), 13 C cross-polarization (CP) MAS NMR, and 14 N NMR are investigated as a function of temperature with a focus on the role of the CH3 NH3 + cation. The molecular motions in (CH3 NH3 )2 MCl4 are also discussed based on the 1 H spin–lattice relaxation time in the rotating coordinate frame T 1ρ . From the 1 H T 1ρ results, the activation energies for the tumbling motion of 1 H for CH3 and NH3 were similar, and the uniaxial rotations occurred within a large temperature range. The molecular motions for 13 C and 14 N of the main chain in the CH3 NH3 + cation were rigid, whereas those for 1 H of the side chain in the CH3 NH3 + cation were very free at high temperatures. T 1ρ provides insight into the changes in the cation reorientation rates induced by heating at high temperatures.